PENGARUH IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK OLI FASTRON DENGAN ATRIBUT PRODUK SEBAGAI VARIABEL MEDIASI - Retno Susanti, Susan Marcelina (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this study is: To analyze the significance of the influence of relationship marketing to the consumer product attributes Oil PT Pertamina Fastron in Surakarta. To analyze the significance of the influence of relationship marketing on consumer purchasing decisions on Oil PT Pertamina Fastron in Surakarta. To analyze the significance of the influence of product attributes on consumer purchasing decisions on Oil PT Pertamina Fastron in Surakarta. To analyze the significance of relationship marketing influence on purchasing decisions mediated by attributes on consumer products Oli PT Pertamina Fastron in Surakarta. In conclusion: Relationship marketing is a significant effect on product attributes on consumer Oli PT Pertamina Fastron in Surakarta. Relationship marketing is significantly influence consumer purchasing decisions on Oil PT Pertamina Fastron in Surakarta. Product attributes significantly influence consumer purchasing decisions on Oil PT Pertamina Fastron in Surakarta. Mediate product attributes relationship marketing influence on consumer purchase decisions on Oil PT Pertamina Fastron in Surakarta. Keywords: relationship marketing, product attributes and purchasing decisions